DAMPAK BEBAN KERJA DAN MASA KERJA TERHADAP KELELAHAN PADA SUPIR TRAVEL - Faiza Rosa, Audrey; Edison, Edison; Elsa Fitri, Wiya; Novita Sary, Annisa; Hasrinal, Hasrinal; Wahyuningsih, Sri; Triana, Wiwin (Ensiklopedia of Journal, 2024)
Fatigue at accurs due to several factors, one of wich is long working hours. Based on the results of an initial survei conducted on 10 drivers, it was found that 7 of the drivers experienced work fatigue. This research was conducted with the aim of looking at the relationship bwtween workload and work period with work fatigue among travel drivers at Po. Ayu Transport Kota Padang in 2023. The study was conducted using a cross sectional design. The population in this study amounted to 60 people. Sampling in this study used a total sampling technique which then obtained a sample of 50 respondents. The data analysis technique used in the study was to use the Chi-Square test. The results of the study found that 41% of respondents experienced high work fatigue, 28% of respondents had a heavy workload and there were 41% of respondents who worked long hours. This study also shows that there is a relationship between workload and work fatigue with the results of the Chi-Square test analysis showing a p-value = 0.0032 (p-value < 0.05) then there is a relationship between working time and work fatigue with the results of the Chi-Square test analysis showing a p-value = 0.043 ( p-value < 0.05). Based on the results of the study, it can be concluded that there is a significant relationship of workload and working period with work fatigue in Po. travel drivers. Ayu Transport Kota Padang in 2023. Therefore, it is expected to the leadership of Po. Ayu Transport Kota Padang to always pay attention to the health of working travel drivers and create health programs to maintain the health of every working driver.Keywords: Work Fatigue, Workload, Working Period